The Evolved Athlete: A Guide for Elite Sport Enhancement - Ivancevic, Tijana; Lukman, Leon.; Gojkovic, Zoran; Greenberg, Ronald; Greenberg, Helen; Jovanovic, Bojan; Lukman, Aleksandar; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This handbook provides insights into becoming a better and more evolved athlete. It offers aspiring athletes, regardless of skill level, a better understanding of their bodies and how to unlock the unlimited potential of muscles without injury. It focuses on the "superhero" muscle: the iliopsoas, and also sheds light on Diamond-Corporation's new technology and elite athleticism, and how these can contribute to a healthier life. Lastly, the authors explore the mindset of success and provide exercises for remaining calm under pressure. This stand-alone book is the sequel to Paradigm Shift for Future Tennis and Enhancing Performance and Reducing Stress in Sport (2014, Springer). This book is written by scientists, whose expertise collectively spans the fields of biomechanics, clinical surgery, current and former elite athleticism, engineering and naturopath doctoral work. Together, they aim to inspire and educate athletes on how to improve their sports performance by using new technologies, world class biomechanics knowledge and ancient herbal medicines.
Introduction -- Mathematical Preliminaries -- Multi-Physical Structure of Human Fascia: Harmony of Biomechanics and Neurodynamics -- Biomechanics of Human Iliopsoas and Functionally Related Muscles -- Exercises, Nutrition and Mental Attitude -- Lymphodynamics and Diamond Sports Matrix System.
Keywords: Computational intelligence; Biomedical engineering; Sports medicine; Human physiology; Computational Intelligence; Biomedical Engineering and Bioengineering; Sports Medicine; Human Physiology